2021
DOI: 10.1002/aelm.202100932
|View full text |Cite
|
Sign up to set email alerts
|

Probing Relaxation Dynamics and Stepped Domain Switching in Boron‐Alloyed VO2

Abstract: The characteristic metal–insulator phase transition (MIT) in vanadium dioxide results in nonlinear electrical transport behavior, allowing VO2 devices to imitate the complex functions of neurological behavior. Chemical doping is an established method for varying the properties of the MIT, and interstitial dopant boron has been shown to generate a unique dynamic relaxation effect in individual B‐VO2 particles. This paper describes the first demonstration of an electrically stimulated B‐VO2 proto‐device which ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Several parameters are known to influence T IMT , such as the synthesis technique and conditions (impacting among other things the vanadium valence state and the amount of intrinsic point defects), the existence of strains in the material (induced by epitaxy or doping) and the eventual addition of a dopant element. In the case of boron doping, it was recently suggested that thermal and time histories might play a crucial role as interstitial boron atoms could diffuse in the VO 2 lattice, leading to a gradual modification of both T IMT and resistivity [18] (and references therein).…”
Section: Morphological and Electrical Propertiesmentioning
confidence: 99%
“…Several parameters are known to influence T IMT , such as the synthesis technique and conditions (impacting among other things the vanadium valence state and the amount of intrinsic point defects), the existence of strains in the material (induced by epitaxy or doping) and the eventual addition of a dopant element. In the case of boron doping, it was recently suggested that thermal and time histories might play a crucial role as interstitial boron atoms could diffuse in the VO 2 lattice, leading to a gradual modification of both T IMT and resistivity [18] (and references therein).…”
Section: Morphological and Electrical Propertiesmentioning
confidence: 99%
“…[74,87] Inclusion of boron also creates pinning sites that cause the phase transition to occur in a step-like manner over a range of applied current or voltage values. [212] While information on the thermally driven MIT for doped VO 2 is extensive, the electrically driven MIT of doped VO 2 thin films remain relatively underexplored.…”
Section: Effect Of Site-selective Modification On Vo 2 Device Behaviormentioning
confidence: 99%
“…As a typical correlated material, VO 2 crystal undergoes significant insulator-to-metal transition (IMT) behavior near 340K, accompanied by great changes in conductivity, infrared transmittance, and other properties. [20][21][22] This unique IMT behavior of VO 2 compound makes it broad applications in the fields of ultrafast photoelectric switching, [23] neuron computing, [24,25] resistive storage, [26] microbrakes, [27] etc. Importantly, the insulator-metal phase transition of VO 2 can be effectively triggered or modulated by various external stimuli such as elemental doping, temperature, electric field, magnetic field, light, and stress.…”
Section: Introductionmentioning
confidence: 99%